The roles, functions and powers of traditional leaders in cooperative governance in the Vhembe District municipality, in the Limpopo Province, post 1994 - Wielenga, Cori (University of Pretoria, 2023)
Dissertation (MA (Political Sciences))--University of Pretoria, 2012.